Research of the Sherabad Epic School Abroad - Kalandarova Dilafruz (Researchparks Publishing, 2022)
The article discusses the participation of the well-known American scientist Walter Feldman in folklore field expeditions during his trip to Uzbekistan in the 90s and the comparison of 2 different versions of the meeting scene of Alpomish and Yodgor from the second part of the